CONCEPTUAL PROVISIONS OF THE THEORY OF STAKEHOLDERS IN THE SYSTEM OF ECONOMIC INTERESTS OF AN AIRPORT - Katerna, Оlga (Proceedings of National Aviation University (archive), 2013)
The article is devoted to theoretical principles of conceptual apparatus of the concept of stakeholders: case study of an airport. There have been proposed the classification of airport stakeholders and their expectations in the process of interaction. Also a model of bilateral relations with major airport stakeholders is presented.